Increasing the Added Value of Wood Powder Waste into Biobriquettes as Renewable Energy Fuel in Nagari Sungai Buluh, Padang Pariaman Regency - Riski Gunawan Nasution; Raihan Aprila; Ririn Arsy Gunawan; Nurfajriana Husna Rahimi; Muhammad Rifan Ridha (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
This community service program aimed to address the problem of wood dust waste in Sungai Buluh Nagari, Padang Pariaman Regency, by converting it into biobriquettes as a renewable energy source. The wood dust waste generated by local woodcrafters has not been utilized optimally and is often burned directly, causing air pollution. Through a participatory approach, this program involved technical training, technology transfer, and hands-on mentoring in biobriquette production. Quantitative analysis through pre-test and post-test of 20 participants showed a significant increase in understanding, with the "highly understood" category surging from 4.2% to 55.0%. Implementation results showed that the community successfully produced functional biobriquettes with specifications of 2 cm diameter, 3 cm height, and a burning duration of 2-3 hours per unit. Community participation reached 93%, with product utilization by satay vendors and households reporting up to 40% savings in fuel costs. This program not only successfully enhanced the economic value of waste but also established independent production groups committed to continuing the biobriquette business sustainably. Support from the village government and community enthusiasm were key success factors, while also contributing to reduced environmental pollution and energy independence at the local level.